2023
DOI: 10.1021/acs.orglett.3c00150
|View full text |Cite
|
Sign up to set email alerts
|

Difluorocarbene-Enabled Synthesis of 3-Alkenyl-2-oxindoles from ortho-Aminophenylacetylenes

Abstract: Herein, we report a transition-metal-free [4 + 1] cyclization pathway from difluorocarbene and ortho-amino aryl alkynone, rendering an effective and universal strategy for the construction of 3-alkenyl-2-oxindoles. Our strategy starts from cheap and accessible ortho-amino aryl alkynone instead of the direct indole skeleton; moreover, in situ generated difluorocarbene from commercially available halogenated difluoroalkylative reagents enables the cleavage of a C–N bond and formation of new C–N bonds and C–C bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Moreover, the reaction gave satisfactory answers with different aromatic and aliphatic amines. 1 H and 13 C NMR, FT-IR, and elemental analysis determined the structure of the nal products. Compound 3c and 5g were also crystallized from EtOAc by slow evaporation at room temperature and the structure was con rmed by Xray crystallographic analysis (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the reaction gave satisfactory answers with different aromatic and aliphatic amines. 1 H and 13 C NMR, FT-IR, and elemental analysis determined the structure of the nal products. Compound 3c and 5g were also crystallized from EtOAc by slow evaporation at room temperature and the structure was con rmed by Xray crystallographic analysis (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Analytical TLC was carried out using Merck 0.2 mm silica gel 60 F-254 Al-plates. 1 H NMR and 13 C NMR spectra were recorded on a Bruker Avance DRX-500 machine using DMSO-d 6 as solvent and TMS as an internal standard at room temperature (DMSO-d 6 1 H NMR: δ (ppm) =2.50 ppm; 13 C NMR: δ (ppm) =39.9 ppm; CDCl 3 1 HNMR: δ (ppm) = 7.26 and 13 C-NMR: δ (ppm) = 77.00 ppm). Chemical shifts were reported in ppm scale.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…77 In 2023, the same group reported that o-aminoarynyne and difluorocarbene precursors followed a [4 + 1] cycloaddition pathway to construct 3-alkenyl-2-oxindole under transition metal-free conditions (Scheme 25a). 78 Difluorocarbene not only promotes breaking of the C-N bond, but also undergoes C-F bond cleavage as a carbonyl source. Various drug candidates could be synthesized through this strategy in moderate to good yields.…”
Section: Cycloaddition and C-f Functionalizationmentioning
confidence: 99%
“…8 b ,10 In all of the above reactions, difluorocarbene functions as a CF 2 source without the loss of any fluorine atom. Recent studies have shown that difluorocarbene can also act as a nonfluorinated C 1 precursor of various functional groups, such as carbonyl, 8 b ,11 cyanide 12 and isocyanide 13 groups (Scheme 1b). The complete loss of the two fluorine atoms is mainly ascribed to the participation of neighboring groups.…”
Section: Introductionmentioning
confidence: 99%